Diskriminācijas aizlieguma princips attiecībā uz brīvu darba ņēmēju un pakalpojumu kustību Eiropas Savienībā - Krastiņš, Uldis (Latvijas Universitāte, 2007)
Diplomdarba tēma ir Diskriminācijas aizlieguma princips attiecībā uz brīvu darba ņēmēju un pakalpojumu kustību Eiropas Savienībā. Diplomdarbā tiek apskatīts diskriminācijas jēdziens kopienas tiesībās; cēloņi kuru dēļ šis princips ir nozīmīgs Kopienā, kā arī principa vēsturisko attīstību. Caur EK Tiesas judikatūras prizmu tiek analizētas dažādas diskriminācijas izpausmes,saistībā ar EK dibināšanas Līguma 39.,49. pantu.

This diploma work is about the non – discrimination principle applied towards free movement of workers and service providers in European Union. Diploma work contains examination of the question of notion of discrimination in the Community law; reasons why the principle of non-discrimination is important for the functioning of the Common market and historical development of the understanding of the word discrimination. Different modes of discrimination – and Articles 39 and 49 of the treaty establishing European Communities are analysed in the light of the case law of the European court of Justice to demonstrate the very different aspects of discrimination in the Community.
The principle of non-discrimination in relation with the free movement of workers and services in European Union
Keywords: Tiesības